COOPERATION WITH INTERNATIONAL ORGANIZATIONS FOR MODERNIZING PUBLIC POLICY OF RISK MANAGEMENT IN CONSTRUCTION - Kharaim I.V. (Pressing Problems of Public Administration, 2018)
The paper emphasizes that cooperation with international organizations is an important aspect of the regional development strategy of every region in Ukraine. Additional opportunities for cooperation with international organizations are determined, in particular, in the sphere of international cooperation in construction risk management. It is pointed out that the activity of modern organizations is performed under the conditions of risk. The author highlights the fact that risk management includes such purpose-oriented actions as risk planning, identi cation, assessment, treatment, control and documentation. Under risk, there appears a need for introduction of the institution of a consultant engineer as a subject of the market of engineering services, and a general understanding of the advantages of applying internationally recognized forms of contracts, speci cally the typical forms of the International Federation of Consulting Engineers (FIDIC).